Small scale biogas technology adoption behaviours of rural households and its effect on major crop yields in East Gojjam Zone of Ethiopia: propensity score matching approach. Issue 1 (31st December 2022) - Chekol, Fasika; Tsegaye, Ashebir; Mazengia, Teshager; Hiruy, Minas
Abstract: The aim of the research was to identify and evaluate the main determinants of small-scale biogas technology adoption and its impact on crop yields. The case study is based on cross-sectional data gathered from 335 rural households in Ethiopia's East Gojjam Zone. This study made use of both primary and secondary data. A questionnaire-based survey was used to collect primary data from 197 biogas adopter (treated) and 138 non-adopter (control) households. Propensity score matching (PSM) methods were used to estimate the determinants and impact of biogas technology adoption on cereal crop yields. According to probit model estimates, the main determinants were cattle head, follow-up and support, extension contact, training access, distance to water sources, and distance to the market. Ethiopian agricultural and rural development policies should consider the impact of household biogas technology adoption behavior when developing policy actions under the Agricultural Transformation Plan.